2010
DOI: 10.1097/phh.0b013e3181ef1935
|View full text |Cite
|
Sign up to set email alerts
|

Integrating HIV Prevention in Reproductive Health Settings

Abstract: RH settings were able to integrate HIV prevention services by employing a systematic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…However, reports of integration benefits represent positive provider perceptions about how well a new system is performing and these perceptions should be taken seriously and seized upon. Perceptions drive provider behaviour, which is central to the long term success of change and integration [11,20]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, reports of integration benefits represent positive provider perceptions about how well a new system is performing and these perceptions should be taken seriously and seized upon. Perceptions drive provider behaviour, which is central to the long term success of change and integration [11,20]. …”
Section: Discussionmentioning
confidence: 99%
“…Once these have been addressed and the transformation accomplished, a subsequent focus should be on how to manage the post-change phase to ensure sustainability of the transformation. Previous work has noted the importance of commensurate staff incentives and benefits ‘packages’ [9,12,25] and that good management of the transformation process is key to sustaining successful change [11,12,26] and effective delivery of health services after transformation [14,21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite some challenges such as staffing norms, technical support, motivation, infrastructural and logistics inadequacies etcetera were identified, the study showed that integration can serve as source of motivation to personnel leading to sharing of work effort. It was also observed in another study that the behaviour of an employee could be central to an organizational change and ultimately determines the outcome of any change process (Zotti et al, 2010). Hence, providers' behavioural response towards the integration of SRH/HIV services can be influenced at an individual level where individual direct benefits may influence their services delivery and at the operational level where health care providers may experience systemic improvements or challenges that may follow an integrated health service (Dudley & Garner, 2011).…”
Section: Literature Reviewmentioning
confidence: 97%
“…However, provision of integrated care from vertical services is very intricate and requires important adjustments in almost all area of health care by organization carrying out public health interventions. The success of any transformation process and its outcome is dependent on the personnel behaviour (Zotti et al, 2010). Health provider's behaviour towards integration can either be at personal level where they can see integration as an opportunity for professional skills enhancement or a threat to their work (Aschraft & ISSN: 2520-3134 Anthony, 2010) and at operational level where providers may experience systemic improvements or challenges that can affect the delivery of integrated services (Maharaj &Cleland, 2005 andMagwaza, Cooper &Hoffman, 2001).…”
Section: Introductionmentioning
confidence: 99%